Population density and spread of COVID-19 in Bandung City, Indonesia - R Syafriharti (Jurnal Planologi, 2022)
Population density is an important factor for a sustainable city. However, it turns out that population density is also a problem in cases of the spread of COVID-19 in several countries, although there are other factors that also play a role. This paper aims to prove how population density affects the spread of COVID-19 in Bandung City with the sub-district data unit. To obtain a complete overview, the analysis was carried out by comparing conditions at the weekend as usual with the conditions during the long weekend. Simple regression analysis was used to determine how population density affects COVID-19 cases. A comparative analysis was then carried out to compare the effect of population density on the number of COVID-19 cases in the two different weekend conditions. The analysis found that population density did affect the number of COVID-19 cases, but this did not apply to all sub-districts. Population density has a greater effect on COVID-19 cases during the usual weekend than during the long weekend. In addition, the best model during the normal weekend only applies to 21 sub-districts, while the best model during the long weekend applies to 26 sub-districts. With these findings, urban planners need an in-depth study of the appropriate concept of population density for a compact and sustainable city.